Pengaruh Tingkat Pendidikan Orang Tua dan Motivasi Belajar Terhadap Nilai Siswa Pada Mata Pelajaran Administrasi Umum Kelas X Otomatisasi dan Tata Kelola Perkantoran Di SMK Negeri 1 Lembah Gumanti - Esa Rahma Agustin; Z. Mawardi Effendi (Universitas Negeri Padang, 2019)
This study aims to determine: (1) The effect of parents 'educational level and learning motivation together on student grades, (2) the influence of parents' educational levels and learning motivation on student scores, (3) the influence of student learning motivation on student grades in general administration subjects in class X Automation and Office Governance in SMK Negeri 1 Lembah Gumanti. This type of research is quantitative research with an associative method using SPSS version 20. The instrument used in this study is a research questionnaire. The existing population of 65 students in the sampling used total sampling with a total of 65 students. The instrument trials used validity and reliability tests. Data analysis with descriptive and inductive analysis using normality test, heterokedasticity test, multicollinearity test, multiple regression test and hypothesis test using F test and t test. From the results of this analysis it can be concluded that: (1) The Level of Parent Education and Learning Motivation together has a positive and significant effect on student scores seen from the value of sig. 0.007 <0.05. (2) There is a negative and insignificant influence on the level of parental education on student scores seen from the Sig. 0.516 > 0.05. (3) There is a positive and significant influence of learning motivation on student grades in general administration subjects seen from the Sig. 0.002 <0.05. Keywords: parental education level, learning motivation, student grad